Development of the ICF-CY Set for Cardiac Rehabilitation After Pediatric Congenital Heart Surgery - Luo, Wen-Yi; Ni, Ping; Chen, Lin; Pan, Qian-Qian; Zhang, Hao; Zhang, Ya-Qing (Frontiers in Pediatrics, 2022)
Background Most children with congenital heart disease (CHD) require surgical repair, and postoperative rehabilitation is an essential step to restore the quality of life. The present study constructs and confirms the International Classification of Functioning, Disability, and Health for Children and Youth core set for children with congenital heart disease 1 year after surgery (ICF-CY-CHDS). Methods From February 2021 to August 2021, 340 children aged 3–6 years after CHD surgery were evaluated using the ICF-CY-CHDS and analyzed using the Rasch model. Results The final ICF-CY-CHDS contained 22 categories; it exhibited a nonsignificant χ2 test result for the item-trait interaction (χ2 = 6736.37, p = 0.8660, Bonferroni-adjusted p = 0.0023). The average severity of children was less than the average difficulty of categories (−2.26 logit <0 logit). The weighted k of all the categories was 0.964 (p < 0.001), and the item separation index was 0.96. The area under the ROC curve of children with a diagnosis result of heart failure was 0.866 (95% CI: 0.801 0.931) with good sensitivity (0.875) and specificity (0.759). Conclusion The ICF-CY-CHDS presents a preliminary practical direction during early cardiac rehabilitation after pediatric CHD surgery, and thus provides a basis and scope for clinical evaluation and intervention program formulation.